Excitability changes in the sciatic nerve and triceps surae muscle after spinal cord injury in mice - Ahmed, Zaghloul; Freedland, Robert; Wieraszko, Andrzej (Journal of Brachial Plexus and Peripheral Nerve Injury, 2010)
Background From the onset to the chronic phase of spinal cord injury (SCI), peripheral axons and muscles are subjected to abnormal states of activity. This starts with very intense spasms during the first instant of SCI, through a no activity flaccidity phase, to a chronic hyperactivity phase. It remains unclear how the nature of this sequence may affect the peripheral axons and muscles.Methods We set out to investigate the changes in excitability of the sciatic nerve and to characterize the properties of muscle contractility after contusive injury of the mouse thoracic spinal cord.Results The following changes were observed in animals after SCI: 1) The sciatic nerve compound action potential was of higher amplitudes and lower threshold, with the longer strength-duration time constant and faster conduction velocity; 2) The latency of the onset of muscle contraction of the triceps surae muscle was significantly shorter in animals with SCI; 3) The muscle twitches expressed slower rising and falling slopes, which were accompanied by prolonged contraction duration in SCI animals compared to controls.Conclusion These findings suggest that in peripheral nerves SCI promotes hyperexcitability, which might contribute to mechanisms of spastic syndrome.